How does aggregate tax policy uncertainty affect default risk? - Mehmet Serkan Tosun; Serhat Yildiz (Journal of Risk and Financial Management, 2020)
We examine the impact of aggregate tax policy uncertainty on firm-level default risk. Due to uncertainties associated with tax policies, firms could have difficulties in determining their optimal debt level and use too much debt to increase their values. This can increase firms' financial risk and default probabilities. At the same time, tax policy uncertainty may lead some firms to take less risk which could lower their use of debt and in turn lower the probability of default. We find that tax policy uncertainty is positively associated with firms' expected default probabilities. In terms of economic significance, our findings show an increase of 14.83% in expected default probability, on a relative basis. Our results are robust to controlling for conditions of the economy, conditions of the stock market, financial constraints of firms, and credit quality of firms. Our evidence adds to two strands of research: research on taxation and firms' risk profiles and the impact of policy uncertainty on firms' decisions.
Keywords: 330; tax policy uncertainty; debt; default risk